Evaluation of the COBAS Amplicor HBV Monitor Assay and Comparison with the Ultrasensitive HBV Hybrid Capture 2 Assay for Quantification of Hepatitis B Virus DNA - Konnick, Eric Q. (American Society for Microbiology, 2005)
Performance characteristics of the COBAS Amplicor HBV Monitor test (Roche Diagnostics), which measures hepatitis B virus (HBV) DNA quantitatively, were evaluated and compared with the Ultrasensitive HBV Hybrid Capture 2 (HC2; Digene Corporation) assay. Linearity and within-run precision were assessed for both methods by using eight HBV DNA-positive samples serially diluted to obtain a range of <100 to 500,000 HBV DNA copies/ml and run in triplicate. Agreement between the methods was studied with 100 clinical samples. HC2 assay performance near the limit of detection was investigated through repeat testing of 149 samples with HC2 and testing of 37 samples with HC2 results of <4,700 HBV DNA copies/ml by Amplicor assay and a qualitative PCR assay. The linearity experiment for Amplicor had regression of observed values compared to expected values (y = 1.073x − 0.247; R(2) = 0.993, n = 32; for HC2, y = 0.855x + 0.759, R(2) = 0.729, n = 18). Within-run standard deviation of log HBV DNA copies/ml ranged from 0.003 to 0.348 (Amplicor) and 0.027 to 0.253 (HC2). Agreement assessed by Deming regression was poor [Amplicor = 1.197(HC2) − 0.961; R(2) = 0.799, standard error of the estimate (SEE) = 0.710, n = 94]. Near the lower limit of detection, 32 of 149 repeat HC2 results were <4,700 HBV DNA copies/ml. Of the 37 samples with HC2 results of <4,700 HBV DNA copies/ml, HBV DNA was not detected in 15 samples, while HBV DNA was detected by at least one PCR method in 12 samples. Amplicor is linear from 200 to 200,000 HBV DNA copies/ml with undiluted samples, and this range can be expanded through dilution. Inconsistent HC2 results near the limit of detection justify use of a grey zone.